MENYISIR LORONG GELAP: TINJAUAN ATAS KEMATIAN KARENA KEKERASAN DALAM RUMAH TANGGA DI INDONESIA - Qonitah Zalikhah Yuselly; Mirna Nur Alia Abdullah (Yayasan Literasi Sains Indonesia, 2025)
Death due to domestic violence is a serious problem that affects many countries, including Indonesia. In cases of domestic violence, this has always been a disturbing issue in Indonesia, with fatal consequences for many victims. This study examines the cultural and socio-economic factors that contribute to death in the context of domestic violence in Indonesia. Using the literature review method, data was collected through search and research results from previous studies. The results of the analysis show that cultural factors such as patriarchal norms and stigmatization of victims can exacerbate violence and increase the risk of death. In addition, socio-economic factors such as economic inequality and access to support services also play a role in increasing vulnerability to death due to domestic violence. These findings provide valuable insights for the development of more effective policies to prevent deaths caused by domestic violence in Indonesia. The 1945 Constitution of the Republic of Indonesia guarantees a sense of security and freedom from all forms of violence, and Law no. 23 of 2004 concerning the Elimination of Domestic Violence (UU PKDRT) recognizes that domestic violence is a violation of human rights that must be eliminated. Therefore, understanding the problem of domestic violence is a form of concern for human dignity and humanity.